A Rare Clinical Presentation of Darier’s Disease - Mybera Ferizi; Antigona Begolli-Gerqari; Bostjan Luzar; Fisnik Kurshumliu; Mergita Ferizi (Case Reports in Dermatological Medicine)
Darier’s disease, also known as keratosis follicularis or dyskeratosis follicularis, is a rare disorder of keratinization. It is an autosomal dominant genodermatosis with high penetrance and variable expressivity. Its manifestation appears as hyperkeratotic papules, primarily affecting seborrheic areas on the head, neck, and thorax and less frequently on the oral mucosa. When oral manifestations are present, the palatal and alveolar mucosae are primarily affected. They are usually asymptomatic and are discovered in routine dental examination. Histologically, the lesions are presented as suprabasal clefts in the epithelium with acantholytic and dyskeratotic cells represented by “corps ronds and grains”. This paper reports a case of a 53-year-old woman that was admitted to our clinic with more than 10-year history of keratotic papules, presented on the hands and feet, nose, ears, genitalia, and whitish lesions on palatal mucosae.